The efficacy of different types of cerebral embolic protection device during transcatheter aortic valve implantation: a meta-analysis - Wang, Chao; Han, Jingjun; Lu, Liuyi; Qiu, Junxiong; Fu, Yuan; Zheng, Junmeng (Frontiers in Cardiovascular Medicine, 2024)
Perioperative stroke remains a devastating complication after transcatheter aortic valve implantation (TAVI), using cerebral embolic protection device (CEPD) during TAVI may reduce stroke rate according to some studies. Therefore, we conducted this meta-analysis and may suggest whether CPED should be routinely used during TAVI. Methods and results: Studies were included which compared the outcome of stroke when with or without CEPD during TAVI, random controlled trials (RCTs) only, and followed up for at least 30 days. The primary end point was stroke (not only cerebrovascular accident but also death due to cerebrovascular accident). The risk of stroke was lower in the CEPD group: RR 0.68, 95% CI 0.49 to 0.96, p = 0.03, I 2 =0%. Subgroup analysis was conducted according to the type of CEPD. The risk of stroke was lower in the I&LCCA (filter cover innominate and left common carotid artery) type CEPD group: RR 0.66, 95% CI 0.49 to 0.96, p = 0.03, I 2 =36%. But the risk of stroke was no significant difference in using the TMCA (filter cover three major cerebral arteries (innominate, left common carotid, and subclavian artery)) type CEPD group: RR 0.81, 95% CI 0.36 to 1.80, p = 0.60, I 2 =0%. Conclusions: In this Meta-analysis, the I&LCCA type CEPD can reduce the risk of stroke within 30 days after TAVI, but the TMCA type cannot.